Development of a Parsimonious Design for Optimal Classification of Exclusive Breastfeeding - Zheng Liu; Aly Diana; Christine Slater; Thomas Preston; Rosalind S. Gibson; Lisa Houghton; Stephen B. Duffull (Wiley, 2019)
A deuterium oxide dose‐to‐mother (DTM) technique is used to determine if an infant is exclusive breastfeeding (EBF). However, the DTM method is intensive, requiring seven paired mother-infant samples during a 14‐day study period. The purpose of this study was to develop a field‐friendly protocol. Data from 790 mother-infant pairs from nine countries were analyzed using a Markov chain Monte Carlo method with Stan. The data were split into (i) model building (565 pairs) and (ii) design evaluation (225 pairs). EBF classification was based on a previously published cut‐off for nonmilk water intake. Classification based on the full design was the reference (gold standard classification). The receiver operating characteristics of parsimonious designs were used to determine an optimal parsimonious classification method. The best two postdose windows (days 7-9 and 13-14) yielded optimal categorization with similar performance in the design evaluation data. This postdose two‐sample design provided 95% sensitivity and specificity when compared with the full design.